2015
DOI: 10.1073/pnas.1505924112
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent recognition of apoptotic and necrotic cells by the human dendritic cell receptor DEC205

Abstract: Dendritic cells play important roles in regulating innate and adaptive immune responses. DEC205 (CD205) is one of the major endocytotic receptors on dendritic cells and has been widely used for vaccine generation against viruses and tumors. However, little is known about its structure and functional mechanism. Here we determine the structure of the human DEC205 ectodomain by cryoelectron microscopy. The structure shows that the 12 extracellular domains form a compact double ring-shaped conformation at acidic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 50 publications
6
44
0
Order By: Relevance
“…In our previous studies, we identified a single mutant (H129E) on the smaller ring that abolished the DEC205 binding to apoptotic and necrotic cells (Fig. 3A) (27). Similarly, ELISA results showed that this mutant had no binding affinity to keratins either (Fig.…”
Section: Dec205 Binds Keratins At Acidic Ph Through Its N-terminal Smmentioning
confidence: 59%
See 4 more Smart Citations
“…In our previous studies, we identified a single mutant (H129E) on the smaller ring that abolished the DEC205 binding to apoptotic and necrotic cells (Fig. 3A) (27). Similarly, ELISA results showed that this mutant had no binding affinity to keratins either (Fig.…”
Section: Dec205 Binds Keratins At Acidic Ph Through Its N-terminal Smmentioning
confidence: 59%
“…Their ectodomains begin with a cysteine-rich domain (CysR), followed by a fibronectin type II domain (FNII) and 8 (10 for DEC205) C-type lectin-like domains (CTLDs). Recently, our data indicate that the ectodomain of DEC205 adopts a double-ringed conformation at acidic pH and also show that DEC205 recognizes apoptotic and necrotic cells specifically in acidic environments through its N-terminal smaller ring (27), suggesting that it mediates a different dead cell recognition pathway from the previously identified receptors. However, because the physiological ligand(s) of DEC205 has not been found, the mechanism of this pathway remains unknown.…”
mentioning
confidence: 57%
See 3 more Smart Citations